The Proline/Arginine Dipeptide from Hexanucleotide Repeat Expanded C9ORF72 Inhibits the Proteasome - Gupta, Rahul (eNeuro, 2017)
An intronic hexanucleotide repeat expansion (HRE) mutation in the C9ORF72 gene is the most common cause of familial ALS and frontotemporal dementia (FTD) and is found in ∼7% of individuals with apparently sporadic disease. Several different diamino acid peptides can be generated from the HRE by noncanonical translation (repeat-associated non-ATG translation, or RAN translation), and some of these peptides can be toxic. Here, we studied the effects of two arginine containing RAN translation products [proline/arginine repeated 20 times (PR(20)) and glycine/arginine repeated 20 times (GR(20))] in primary rat spinal cord neuron cultures grown on an astrocyte feeder layer. We find that PR(20) kills motor neurons with an LD(50) of 2 µM, but in contrast to the effects of other ALS-causing mutant proteins (i.e., SOD or TDP43), PR(20) does not evoke the biochemical signature of mitochondrial dysfunction, ER stress, or mTORC down-regulation. PR(20) does result in a time-dependent build-up of ubiquitylated substrates, and this is associated with a reduction of flux through both autophagic and proteasomal degradation pathways. GR(20), however, does not have these effects. The effects of PR(20) on the proteasome are likely to be direct because (1) PR(20) physically associates with proteasomes in biochemical assays, and (2) PR(20) inhibits the degradation of a ubiquitylated test substrate when presented to purified proteasomes. Application of a proteasomal activator (IU1) blocks the toxic effects of PR(20) on motor neuron survival. This work suggests that proteasomal activators have therapeutic potential in individuals with C9ORF72 HRE.